Analyzing the Culture of Corruption in Indian Higher Education - Tierney, William G.; Sabharwal, Nidhi S. (International Higher Education, 2016)
Academic corruption occurs in all institutions and all countries. It is, however, an area of research that is often difficult to study. The intent here is to understand what systemic corruption is and how it is done in India. The authors find a broken culture which enable corrupt practices to occur throughout the system.